Value-Based Performance Excellence Model: Case Studies at Malaysian Technical Universities - M. R., Abdul Hamid (AENSI Publishing, 2011)
This article discussed the case studies of performance excellence model at Technical Higher Education Institution (HEI) in Malaysia. The model integrates core values as performance indicators in six performance criteria i.e. leadership, culture, productivity focus, employee focus, stakeholder focus and performance results. 400 questionnaires were distributed to all technical universities and resulted 240 questionnaires being returned. Multivariate statistical analysis through Structural Equation Modeling (SEM) was used to analyse the model by using Maximum Likelihood (ML) estimation and yielded an adequate fit statistics for normed chi-square = 2.578, CFI = 0.916, TLI= 0.909 and RMSEA = 0.086. In addition, Bayesian estimation was further employed to cross-validate and support the modeling result obtained from ML estimation. The Bayesian SEM indicated that the results produced from ML estimation is almost similar and acceptable. In conclusion, the Performance Excellence Model for Malaysian Technical Universities is admissible as it has been empirically tested. This performance excellence model could be used for HEI especially the technical universities to empower intangibles performance measurement through value-based indicators.